Clinical study on real-time three-dimensional CT navigation-guided full-endoscopic lumbar interbody fusion - Yang, Yang; Dong, Jianwen; Liu, Zhongyu; Chen, Ruiqiang; Chen, Zihao; Zhai, Zhengjia; Qi, Jiakun; Rong, Limin (Zhongguo xiu fu chong jian wai ke za zhi, 2022)
To analyze the technical notes, effectiveness, and current issues of real-time three-dimensional CT navigation-guided full-endoscopic lumbar interbody fusion.ObjectiveTo analyze the technical notes, effectiveness, and current issues of real-time three-dimensional CT navigation-guided full-endoscopic lumbar interbody fusion.Between April 2020 and October 2021, a total of 27 patients received real-time three-dimensional CT navigation-guided full-endoscopic lumbar interbody fusion. There were 18 males and 9 females with an average age of 63.2 years (range, 48-84 years). There were 6 cases of lumbar spinal stenosis, 1 case of lumbar instability, 9 cases of lumbar spinal stenosis with instability, 3 cases of degenerative spondylolisthesis, 6 cases of isthmus spondylolisthesis, and 2 cases of recurrent lumbar disc herniation. All patients showed neurological symptoms before operation (ipsilateral symptom for 15 cases and bilateral symptom for 12 cases). The symptom duration was 1-300 months (median, 24 months). The